VD_FINDINFO ML / 2014 / 178 vom 10. Juli 2014 - VD Tribunal cantonal (2014)
RECONNAISSANCE DE DETTE, SIGNATURE, REPRÉSENTANT, HONORAIRES, AVOCAT | 82 LP, 105 al. 2 CPC (CH), 106 al. 1 CPC (CH), 95 al. 3 let. b CPC (CH), 20 al. 2 TDC, 6 TDC